Comparative evaluation of BacT/ALERT VIRTUO and BACTEC FX400 blood culture systems for the detection of bloodstream infections - Yurong Qin; Yiwen Liao; Jingfang Zhou; Weijiang Liu; Huimin Chen; Xiaoli Chen; Weisha Wang; Ni Zhang; Yunhu Zhao; Liang Wang; Bing Gu; Suling Liu (Microbiology Spectrum)
ABSTRACT Bloodstream infections (BSI) pose significant threats to patient health, necessitating timely and accurate diagnostics to reduce mortality and morbidity. This study aimed to evaluate the clinical performance of the BacT/ALERT VIRTUO blood culture system with FANPlus bottles compared to the BACTEC FX400 system in detecting bloodstream pathogens. A total of 1,772 blood specimens were collected from various hospital wards. Specimen selection criteria were based on clinical suspicion of bloodstream infections, ensuring the inclusion of relevant and representative patient samples. These blood samples, collected from the same suspected sepsis patients, were cultured in parallel using both the BacT/ALERT VIRTUO and BACTEC FX400 systems. The diagnostic efficiency of both systems, including detection rates, time to detection (TTD), and sensitivity across different bacterial species, was assessed. In various application scenarios, the VIRTUO system demonstrates a higher positive detection rate, whether in the intensive care unit (ICU) (8.5% vs 6.4%, P = 0.028) or in general wards. Additionally, for different types of bacteria, the TVIRTUO system exhibits superior detection rates for anaerobic bacteria (5.9% vs 3.2%, P < 0.001) and aerobic bacteria (9.1% vs 7.2%, P = 0.043). Furthermore, it boasts a shorter median TTD of 14 hours compared to 16 hours, and a higher sensitivity for Gram-positive bacteria (2.8% vs 1.6%, P < 0.001). These findings emphasize VIRTUO’s effectiveness in enhancing diagnostic accuracy, achieving faster time to detection, and expanding the spectrum of detected organisms, thereby facilitating the quicker initiation of appropriate therapies, supporting precise clinical decision-making, and ultimately improving patient outcomes.IMPORTANCEOur study conducted a critical evaluation of advanced blood culture technologies for managing bloodstream infections (BSI). A distinctive strength of our research is the large sample size and the concurrent testing of the same patients with two systems, a methodology rarely achieved in other studies. BSIs present severe health threats, necessitating prompt and accurate diagnostics to mitigate morbidity and mortality. The BacT/ALERT VIRTUO system, in comparison to the BACTEC FX400 system, demonstrated superior detection capabilities, emphasizing the critical role of advanced diagnostics in clinical settings.